Towards a typology of childhood internal mobility: Do children of migrants and non‐migrants differ?. Issue 2 (11th October 2021) - Kuyvenhoven, Joeke; Das, Marjolijn; de Valk, Helga A. G.
Abstract: Moving during childhood is an important life event that is often stressful and potentially disruptive. With the majority of existing studies on childhood internal mobility using a one‐dimensional measure of mobility and focusing on the total population, there is still limited knowledge on differential childhood mobility patterns for children of different migrant origins. In this study, we acknowledge the multidimensional nature of mobility by covering frequency, timing, distance, and change in place type to understand internal mobility patterns for children aged 0–16 without and with different second‐generation migrant backgrounds. Internal mobility is analysed for children born in the Netherlands between 1995 and 2003 using longitudinal full population register data. K‐means cluster analysis reveals five types of mobility: nearby preschool‐aged, nearby school‐aged, long‐distance to more densely populated areas, long‐distance to less densely populated areas, and frequent movers. Results of multinomial logistic regressions show that having a second‐generation migrant background increases the likelihood of being in any of the mobility clusters and reveals variation in types of mobility patterns for different migrant origin groups. We conclude that childhood mobility patterns are diverse and overall more often experienced by children of second‐generation migrant origin potentially adding to a more vulnerable situation and inequality over the life course.